Commentaires sur la critique de Ronald Rudin - Dickinson, John A. (Bulletin d'histoire politique, 1995)
Un article de la revue Bulletin d'histoire politique, diffusée par la plateforme Érudit.

Les Populations Amérindiennes De La Vallée Laurentienne, 1608-1765 - Dickinson, John A.; Grabowski, Jan (Annales de démographie historique, 1993)
L'historiographie de la dynamique démographique des populations américaines a beaucoup insisté sur leur chute dramatique suite au choc microbien. En raison de sources relativement abondantes, la vallée du Saint-Laurent constitue une aire privilégiée pour l'observation de l'évolution des populations autochtones. Suite à une première série d'épidémies dans les années 1630, les effectifs baissent d'environ 500 à environ 200 individus. Ces pertes sont compensées par des migrations importantes de Hurons dès les années 1650, et d'Irocmois et d'Abénakis par la suite, qui permettent de largement dépasser les effectifs initiaux. Au XVIIIe siècle, la population des villages auprès des défrichements français se stabilise autour de 2 500 individus et se gonfle jusqu'à plus de 4 000 en temps de guerre avec l'arrivée des réfugiés. Les résultats de cette enquête soulignent la capacité des populations amérindiennes à se maintenir et même à croître sur un territoire donné, longtemps après l'arrivée des Européens ainsi que l'importance des migrations dans la dynamique démographique autochtone. The literature concerning colonial American populations has emphasized their dramatic decline as a result of the impact of European disease. The relative abundance of source material facilitates the observation of the evolution of native populations in the St. Lawrence valley. Following an initial series of epidemics in the 1630s, the population declined from about 500 to 200 individuals. This decline was compensated for by important migrations of Hurons in the 1650s and Iroquois and Abenakis thereafter. By 1675, the native population of the St. Lawrence valley surpassed that of the immediate precontact period. The population of the native villages close to French settlements stabilized around 2 500 people during the eighteenth century, and rose to over 4 000 in wartime with the influx of refugees. The results of this study underline the fact that native populations in a given territory could stabilize and even increase long after the arrival of Europeans and the importance of migrations to understand Indian population dynamics.

Native Sovereignty and French Justice in Early Canada - Dickinson, John A. (Essays in the History of Canadian Law, 1994)
As native territorial claims and the issue of self-government become increasingly important on the Canadian political agenda, questions of native sovereignty in historical context take on new meaning. The United States recognizes Indian nations as sovereign entities to whom the federal government is legally bound to carry out its ‘trust responsibility’¹ Canada has not followed this lead, and although some recent decisions – notably the Sparrow (1987) and Sioui (1990) cases – have been more generous in recognizing native claims,² aboriginal rights are never taken for granted. In recent Quebec cases, for example, the Crown has tried to prove that